Cooperative organizations of small molecular surfactants and amphiphilic block copolymers: Roles of surfactants in the formation of binary co‐assemblies. Issue 6 (3rd May 2021) - Cao, Yuanyuan; Yang, Shaobo; Li, Yongsheng; Shi, Jianlin
Abstract: The construction of highly ordered organizations through self‐assembly is one of the most popular phenomena both in natural and artificial environments. Amphiphilic molecules are the most commonly used building blocks for the self‐assembly, which are conventionally known as amphiphilic low molecular weight surfactants with polar heads and nonpolar tails, or amphiphilic block copolymers (BCPs) consisting of covalently bonded hydrophilic and hydrophobic block chains. Compared with single surfactant self‐assembly system, binary amphiphiles co‐assembly systems composing of both small mass surfactants and amphiphilic BCPs feature high flexibilities and versatilities in materials designing and structure regulation, ascribing to the vast possibilities of intermolecular interactions within the systems and facile component modulations during the assembly processes. The amphiphilic features of the two kinds of molecules endow them with similar self‐assembly behaviors, while the unique and distinct characters of each kind of amphiphiles lead to various complex but highly diversified co‐assembly systems. According to the roles of the surfactant played in the co‐assembly system, in this review, we summarize the binary co‐assembly systems from three distinct types: 1) the co‐micellization system in which the surfactants are added into the BCPs assemblies as a self‐assembly assistant; 2) the co‐emulsification system in which the surfactants work as an emulsion stabilizer to assist and confine the assembly of BCPs in 3D geometries; 3) the co‐templating system where the individual micelles of both surfactant and BCPs are hierarchically arranged and distributed to guide the formation of hierarchical nanomaterials. Following this, the major potential applications of the nanomaterials synthesized from the binary amphiphiles in biological field are described. Finally, we shortly discuss the current challenges and future perspectives of the binary amphiphiles self‐assembly systems. Abstract : The binary co‐assembly systems composing of amphiphilic block copolymers and surfactants have provided us with a versatile platform for materials design and appropriate models for exploration the complex natural self‐assembly mechanism. According to the roles of the surfactant played in the co‐assembly system, recent developments including the co‐micellization, the co‐emulsification, and the co‐templating binary amphiphiles systems are summarized in this review.